Active Manipulation of Functional Droplets on Slippery Surface. (31st August 2022) - Han, Keyu; Wang, Zubin; Han, Xiao; Wang, Xuan; Guo, Pu; Che, Pengda; Heng, Liping; Jiang, Lei
Abstract: Droplet manipulation has drawn enormous attention due to its important role in technological applications from energy and environment to human health. However, the facilely active manipulation of functional droplets on a nonresponsive slippery surface remains a great challenge. Here, triggered by external stimuli (light irradiation, electric field, and magnetic field), an active manipulation of functional droplets is reported, that is propelling the droplets on a nonresponsive slippery surface, without the need fosurface responsiveness. The driven forces are the asymmetrical forces induced by external stimuli. Moreover, the proof‐of‐concept experiments of the coalescence, micro reaction, anti‐gravity force manipulation, and screening of different droplets under external stimuli are demonstrated. All the results indicate that this work can offer a feasible strategy for actively manipulating droplets independent of surface responsiveness and facilitate the development of chemical detection, microfluidics, bioanalysis, and medicines. Abstract : Droplet manipulation and transport are ubiquitous in biological processes and indispensable in technological applications. Here, active manipulation of functional droplets on nonresponsive slippery surface triggered by light irradiation, electric field, and magnetic field is reported, which can be used for the coalescence, microreaction, anti‐gravity force manipulation, and screening of different droplets.